2018
DOI: 10.1182/bloodadvances.2018022053
|View full text |Cite
|
Sign up to set email alerts
|

Direct modulation of the bone marrow mesenchymal stromal cell compartment by azacitidine enhances healthy hematopoiesis

Abstract: Key Points• AZA treatment of MSCs in MDS leads to preferential expansion of healthy over malignant hematopoiesis.• AZA regulates key MSC genes crucial for support of hematopoiesis, providing proof of concept for epigenetic therapy of MSCs in MDS. Mesenchymal stromal cells (MSCs) are crucial components of the bone marrow (BM) microenvironment essential for regulating self-renewal, survival, and differentiation of hematopoietic stem/progenitor cells (HSPCs) in the stem cell niche. MSCs are functionally altered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
3
37
1
Order By: Relevance
“…Since MDS-MSCs have different methylation patterns compared to their healthy counterparts ( Geyh et al., 2013 ), it begs the question if HMA-induced changes in the BME contribute to the clinical responses observed. To this end, 5-Aza enhances the ability to support normal hematopoiesis in MDS-MSCs, while decreasing their support for MDS HSPCs ( Wenk et al., 2018 ; Poon et al., 2019 ). During disease homeostasis, MDS-induced impairment of MSCs' functions appears reversible by 5-Aza but only up to a certain point in disease progression ( Poon et al., 2019 ).…”
Section: Current Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since MDS-MSCs have different methylation patterns compared to their healthy counterparts ( Geyh et al., 2013 ), it begs the question if HMA-induced changes in the BME contribute to the clinical responses observed. To this end, 5-Aza enhances the ability to support normal hematopoiesis in MDS-MSCs, while decreasing their support for MDS HSPCs ( Wenk et al., 2018 ; Poon et al., 2019 ). During disease homeostasis, MDS-induced impairment of MSCs' functions appears reversible by 5-Aza but only up to a certain point in disease progression ( Poon et al., 2019 ).…”
Section: Current Therapiesmentioning
confidence: 99%
“…5-Aza restored the hematopoiesis-supporting capacity of most primary MDS-MSCs samples derived from low grade MDS but not those from advanced-stage disease ( Poon et al., 2019 ). However, treatment with 5-Aza is capable to enhance hematopoiesis-supporting properties of healthy MSCs as well, suggesting that the effect is not specific to MDS-induced changes ( Wenk et al., 2018 ). It is currently unknown what molecular program induced by azanucleotides rescue MSC function.…”
Section: Current Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the hypomethylating agent azacytidine was reported to target stromal niche compartments in addition to its well-known effect on neoplastic hematopoietic cells. Azacytidine-treated MSCs displayed enhanced potential to promote healthy hematopoiesis [ 75 ]. Another study reported comparable effects in an MDS xenograft model [ 76 ].…”
Section: Novel Therapeutics Targeting Niche Componentsmentioning
confidence: 99%
“…Genetic manipulation of feeder layers has been shown to impart better yield of HSCs. Wenk et al [55] showed that 5Azacitidine (5Aza) treatment of MSCs isolated from both, normal and myelodysplastic syndromes marrows resulted in their epigenetic modulation and these 5Aza-modulated MSCs supported the growth of normal HSCs over leukemic HSCs. However, in this study only colony formation assay was used as a read out and in vivo transplantation studies were not done.…”
Section: Priming Of Mscs To Enhance Hsc Engraftmentmentioning
confidence: 99%